Müller Glia to Müller Glia Extracellular Vesicle-Dependent Signaling Induces Multipotency Genes and l Expression in Response to N-methyl-D-aspartate (NMDA) Exposure - Ana Karen Carapia; Erick J. Martinez-Colin; Deisy Segura-Villalobos; Rebeca Yael Victoria-Chavez; Ivonne Lezama; Eduardo Martinez-Martinez; Monica Lamas (ASN Neuro, 2023)
A strict localization into the neural retina and the capacity to survive many pathogenic conditions are unique characteristics of Müller glia. Retinal damage induces cellular and molecular changes that place Müller cells as focal points to either protect or further impair neuronal function. This work evaluated the involvement of extracellular vesicles (EVs) in the transduction of high N-methyl-D-aspartate (NMDA) concentration signal between Müller glia-to-Müller glia as part of several factors and signal transduction mechanisms dictating either a gliotic (damaging) or regenerative process. These EVs were obtained, characterized, and quantified from control and NMDA-treated Müller cells using murine Müller cell primary cultures to evaluate the functional outcome of these preparations. The obtained results support the existence of different subpopulations of EVs that may induce a differential response. These EVs did not affect the viability, migration, and wound healing capacity of cultured Müller cells. However, the EVs obtained from NMDA-treated Müller cultures, but not from untreated cells, increased actin polymerization and induced the expression of the multipotency genes nestin and lin28 . We propose that, upon a lesion paradigm, Müller-derived EVs may induce the spread of molecular changes in neighboring cells resulting in the formation of the characteristic glial retinal scar in mammalians or else trigger a neurogenic process in regenerative species. Summary Statement Retinal Müller cells secrete extracellular vesicles that can be captured by other Müller cells. In response to a signal that may be deleterious for the retina, Müller glia-derived extracellular vesicles spread instructions to induce gene expression changes in other cells.